2021
DOI: 10.1542/hpeds.2020-001388
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Adverse Events in Children Receiving Outpatient Parenteral Antibiotic Therapy

Abstract: BACKGROUND: Outpatient parenteral antibiotic therapy (OPAT) can decrease length of hospital stay but is associated with adverse events (AEs). The purpose of this study was to quantify and identify risk factors for OPAT-associated AEs in children. METHODS: Retrospective single-center study of children ≤21 years old discharged on OPAT from January 2016 to April 2019 with infectious diseases follow-up. Demographic and clinical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…34 This study is the largest utilizing only peripheral vascular access compared to other studies where CVCs were used. 6,30,31 Our study supported previous ones that showed this service is possible and achievable with no serious adverse effects. We provided the first IV dose in the PED and then discharged the patient with a "capped" IV catheter and instructions to come back to a specific area in the ED for the subsequent doses of IV antibiotics and safety reassessment.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…34 This study is the largest utilizing only peripheral vascular access compared to other studies where CVCs were used. 6,30,31 Our study supported previous ones that showed this service is possible and achievable with no serious adverse effects. We provided the first IV dose in the PED and then discharged the patient with a "capped" IV catheter and instructions to come back to a specific area in the ED for the subsequent doses of IV antibiotics and safety reassessment.…”
supporting
confidence: 89%
“…We consider the total number of patients in our study relatively high compared to other series. [28][29][30][31][32] The OPT unit is in the same building of the main PEC but managed by medical and nursing team independent of the PEC coverage. Therefore, almost 90% of the patients who were referred to the OPT unit were from the main PEC, and the remaining were from PEC satellites or other institutional EDs with no patients from the hospital wards.…”
mentioning
confidence: 99%
See 1 more Smart Citation